3-4x=x+7

Simple and best practice solution for 3-4x=x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-4x=x+7 equation:


Simplifying
3 + -4x = x + 7

Reorder the terms:
3 + -4x = 7 + x

Solving
3 + -4x = 7 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3 + -4x + -1x = 7 + x + -1x

Combine like terms: -4x + -1x = -5x
3 + -5x = 7 + x + -1x

Combine like terms: x + -1x = 0
3 + -5x = 7 + 0
3 + -5x = 7

Add '-3' to each side of the equation.
3 + -3 + -5x = 7 + -3

Combine like terms: 3 + -3 = 0
0 + -5x = 7 + -3
-5x = 7 + -3

Combine like terms: 7 + -3 = 4
-5x = 4

Divide each side by '-5'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 8-3x/5=2x/3-14/3 | | 1/3x=x-14 | | 40x+20y=5600 | | -5(p+2)=6-p | | 2(6w-5)=3(4w-1)-8 | | 9t=4(2t-5) | | 9-2(x-7)=7(x-7) | | 2-5(x+1)=5-3x | | 5(x+1)2+2=22 | | 2(8x-3)=20x-58 | | y=67x-7 | | 2(3x+1)=6-3x | | .50x+5=1x | | 7-3(4-x)=-26 | | 5-2(x+1)=17 | | -2(x+1)=5 | | 3(4y-4)-y=11 | | 6x-12x-5=0 | | 1/9x-5/3=0 | | 12(1/4)-8(3/10) | | 12x-4=3(x+1)-x | | 6x-4y=-20 | | 7÷2(1/5) | | -8*7-7y=56 | | 7x^2+5x-14=34-29x | | cosx=7x | | y=6x^2+6 | | X-8+1=3x | | -8*8-7y=56 | | 2+5x=6*(x-4) | | -8-8-7y=56 | | -8-8-7=56 |

Equations solver categories